Axial Compression Behaviour of Cross-Laminated Wood-Wool Cement Composite Panel Wallette Bonded With Lightweight Cement Mortar - Bahari, Muhammad Hazim Fahmi; Md Noh, Mohammad Soffi (Recent Trends in Civil Engineering and Built Environment, 2021)
Wood-wool cement composite panel is one of wood-based composite material that produced in stable panel form and suitable to be used as building wall system to replace non-eco-friendly material such as brick and other masonry elements. Heavy construction material such as brick requires more manpower and consumes a lot of time to build the wall panel. WWCP is a lightweight material with density range from 400 kg/m3 to 1850 kg/m3 and also capable to support an imposed load from the building. This study was conducted to investigate an axial compression behavior prefabricated reinforced wallettes constructed with two layers of wood-wool cement panel at a cross wise orientation. The two layers of WWCP was be bonded with 15 mm thickness lightweight mortar paste. As to improve the load-carrying capacity, the wallettes specimens where be reinforced with A6 wire mesh provided at the middle of mortar paste. Three replicates of wallettes specimen with dimension 900 mm width and 900 mm length were tested under axial compression load after 28 days of fabrication. The results indicated that the wallettes have the ability to sustained maximum axial compression load of 93kN. This shows that the new arrangement technique of cross-laminated wood-wool panel was observed as this technique can withstand a higher axial compression load test better than the single orientation technique either only longitudinal or horizontal arrangement.